Pelelangan Proyek Konstruksi Berbasis Internet - Tanubrata, Maksum; Wiryopranoto, Hendaryanto (Jurnal Teknik Sipil, 2019)
Procurement implementation by auction can be done efficient, effective and comparable, transparent, fairness, not discriminative and accountable with the system which can accommodate the above criteria.With the fast development of information technology the above implementation can be realized with the online auction system base on internet by web. E-procurement, it is an application for auction implementation by electronic with internet basis where web as an implementation medium. This application can be used as an announcement, document storage also as a tool in selection process. With internet base the interaction between buyers and vendors can be optimized without any limitation in distance and time.